FRI0404 Characterisation of a monocytes/macrophages cell subset co-expressing both m1 and m2 phenotype markers in systemic sclerosis patients. (12th June 2018) - Soldano, S.; Trombetta, A.C.; Ruaro, B.; Tomatis, V.; Brizzolara, R.; Montagna, P.; Paolino, S.; Pizzorni, C.; Smith, V.; Contini, P.; Sulli, A.; Cutolo, M.
Abstract : Background: In the pathogenesis of systemic sclerosis (SSc), the immune cell activation is an important event that includes alteration in the macrophage polarisation. 1 Macrophages may polarise into classically activated (M1), which are characterised by the expression of specific markers such as Toll-like receptors (TLR2 and 4) and costimulatory molecules (CD80 and CD86), or alternatively activated (M2), which are characterised by the expression of specific phenotype markers such as mannose receptor-1 (CD206) and macrophage scavenger receptors (CD204 and CD163). M2 are present in the circulation and in the skin infiltrate of SSc patients (pts), where they seem to contribute to fibrosis. 2–4 Objectives: To characterise circulating M2 monocytes/macrophages from SSc pts and healthy subjects (HSs) by their co-expression of CD204, CD163 and CD206, as well as cells expressing both M1 and M2 phenotype markers. Methods: Fifty-eight SSc pts (54 females/4 males, mean age 63±13 years), fulfilling the new EULAR/ACR criteria for SSc, and 27 age-matched HSs were consecutively enrolled after Informed Consent was obtained. Peripheral blood was collected and the antibodies CD14-APC-Vio770 and CD45-VioGreen were used to identify the monocyte/macrophage lineage; CD204-VioBright-FITC, CD163-PE-Vio770 and CD206-PeerCP-Vio700 were used to characterise the M2 phenotype, whereas CD80-APC, CD86-VioBlue, TLR4-PE and TLR2-PE-Vio615 were used to characterise the M1 phenotype (Miltenij Biothech). Flow Cytometry analysis was performed using Navios Flow Cytometer and the related Navios analysis software (Beckman Coulter). Results: In the CD14 + cell subset (monocytes), the CD14 + CD163 + CD206 + CD204 + cell percentage was significantly increased in SSc pts compared to HSs (p=0.02). Inside the CD14 + CD163 + CD206 + CD204 + monocytes/macrophages a subset of cells co-expressing also TLR4, CD80 and CD86 was detected. This mixed population (M2/M1) of cells was significantly increased in SSc pts compared to HSs (p=0.003). At the same time, circulating monocytes/macrophages showing a full M2 phenotype and characterised as CD204 + CD163 + CD206 + cells were investigated independently of the expression of CD14, and they also resulted significantly increased in SSc pts compared to HSs (p<0.0001). In the CD204 + CD163 + CD206 + cell subset (M2), the percentage of cells expressing also TLR4, CD80 and CD86 (M1) was significantly increased in SSc pts compared to HSs (p<0.0001). Conclusions: These results describe for the first time a subset of circulating cells belonging to the monocyte/macrophage lineage with a mixed phenotype, which are characterised by the expression of both M1 and M2 surface markers. These cells were observed to be increased in the peripheral blood of SSc pts compared to HSs, suggesting their possible role in the pathogenesis of the disease. References: [1] Stifano G, et al. Curr Rheumatol Rep2016;18:2. [2] Higashi-Kuwata N, et al. Arthritis Res Ther2010;12:R128. [3] Wynn TA, et al. Immunol Rev. 2016;44:450–62. [4] Christmann RB, et al. Arhtitis Rheum. 2011;63:1718–28. Disclosure of Interest: None declared